Making Self-Regulation More Than Merely Symbolic: The Critical Role of the Legal Environment - Short, Jodi L.; Toffel, Michael W. (Administrative Science Quarterly, 2010)
Using data from a sample of U.S. industrial facilities subject to the federal Clean Air Act from 1993 to 2003, this article theorizes and tests the conditions under which organizations' symbolic commitments to self-regulate are particularly likely to result in improved compliance practices and outcomes. We argue that the legal environment, particularly as it is constructed by the enforcement activities of regulators, significantly influences the likelihood that organizations will effectively implement the self-regulatory commitments they symbolically adopt. We investigate how different enforcement tools can foster or undermine organizations' normative motivations to self-regulate. We find that organizations are more likely to follow through on their commitments to self-regulate when they (and their competitors) are subject to heavy regulatory surveillance and when they adopt self-regulation in the absence of an explicit threat of sanctions. We also find that historically poor compliers are significantly less likely to follow through on their commitments to self-regulate, suggesting a substantial limitation on the use of self-regulation as a strategy for reforming struggling organizations. Taken together, these findings suggest that self-regulation can be a useful tool for leveraging the normative motivations of regulated organizations but that it cannot replace traditional deterrence-based enforcement.